Benchmarking the calculation of electrically insulating properties of complex gas mixtures using a multi-term Boltzmann equation model. (6th October 2021) - Flynn, M; Neuber, A; Stephens, J
Abstract: The accurate calculation of DC breakdown voltage thresholds solely from elementary electron-neutral interactions in complex gas mixtures using a multi-term Boltzmann equation (BE) kinetic model is demonstrated. SF6 :N2 mixtures in the 100 Td < E / N < 400 Td field regime are explored to benchmark the model's effectiveness. A ten-term BE model is found to yield DC breakdown voltages which, on average, agree within 3% of experimental measurements. A two-term BE model is also applied in order to characterize the error introduced in all calculations by the two-term approximation. These discrepancies are largest in pure N2 where error is greater than 10% for diffusion coefficients, within 6% for particular vibrational rate coefficients, and within 5% for breakdown voltages. However, this error falls to within 1% for most parameters and breakdown voltages in mixtures with large SF6 content.